2022
DOI: 10.29185/hayuretim.978601
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Economical Aspect of Water Buffalo Farming: A Case Study of Balıkesir Province

Abstract: Amaç: Türkiye’de 2010 yılı sonrasında manda ürünlerinin değerinin anlaşılması ve uygulamaya geçirilen projelerin de etkisiyle manda yetiştiriciliği önem kazanmıştır. Bu çalışmada Balıkesir ilinde Halk Elinde Manda Islahı Projesi kapsamındaki manda işletmelerinin ekonomik yönü ortaya konulmuştur.Materyal ve Yöntem: Araştırmanın verileri Balıkesir ilinde manda sütü üretiminin yoğun olarak yapıldığı Altıeylül ile Gönen ilçelerinde bulunan toplam 102 üreticiden anket yoluyla elde edilmiştir. Araştırma kapsamında m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…All of these results were found to be lower than the values obtained from Anatolian Water Buffaloes reared in Igdir province. The milk amount (2229.87±93.70 kg/ lactation) obtained by Pawar et al, (2012) for Murrah water buffaloes in Punjab, Ludhiana, India and the milk amount (1332.89 kg/lactation) obtained by Saner et al, (2022) for water buffaloes in Balıkesir province was found to be higher when compared with this study.…”
Section: Discussioncontrasting
confidence: 73%
“…All of these results were found to be lower than the values obtained from Anatolian Water Buffaloes reared in Igdir province. The milk amount (2229.87±93.70 kg/ lactation) obtained by Pawar et al, (2012) for Murrah water buffaloes in Punjab, Ludhiana, India and the milk amount (1332.89 kg/lactation) obtained by Saner et al, (2022) for water buffaloes in Balıkesir province was found to be higher when compared with this study.…”
Section: Discussioncontrasting
confidence: 73%
“…Soysal et al (2005) found in his study that 79% of the participants were aged between 18-60 years and 93 % of them graduated from at least primary school while 7% of them did not receive any education. Saner et al (2022) reported that the average age of buffalo breeders was 45.89 years and received education for an average of 6.58 years. Şeker et al (2012) found that 8.0% of the breeders in Muş were not literate, 38.4% of them graduated from primary school while 2.4% of them graduated from university.…”
Section: Resultsmentioning
confidence: 99%
“…When these participants were asked to explain the reasons for thier dissatisfaction, they expressed the difficulties they experienced in terms of caring for buffaloes general livestock raising problems such as high fodder prices, inadequacy of support and lack of marketing. In a study conducted in Balıkesir, it was found that the breeders intended to make new investments in buffalo breeding in the upcoming periods and that this situation will continue to be more widespread (Saner et al, 2022). In his study Karadavut et al (2010) found that 87.18 % of the breeders were not satisfied with breeding.…”
Section: Figure 1 Reasons Of the Participants To Raise The Water Buffalomentioning
confidence: 99%
See 2 more Smart Citations